The Beginning of Creation between Judaism and Islam - A Comparative Study - - Shindakh , Luay (Islamic Sciences Journal, 2023)
And because he found himself in the Qur’an, he found his link in the Qur’an (we wrote on the people of Israel). The first was built on Israel in the Torah. History was the first sentence in the Qur’an (friendship, angels, arrogance, seventh, but it was in the Qur’an(. The points of convergence and separation between the Book of Genesis and the Noble Qur’an in the creation of the universe: As a result of the discussion of the creation of the universe in the six days between the Book of Genesis and the Holy Qur’an, both books agree on the number of roles of creation that they are six, and they also agreed that the stars are the source. However, they differed that the Noble Qur’an is unique from what the aforementioned book did not mention, and that the emergence of the universe came with a great explosion, and that the six roles are stages and not days of a human analogy as pictured. in the Torah. The Holy Qur’an also singled out the description of the initial state at the beginning of the process of creating the universe with the gaseous state of "smoke", which corresponds to the realities of the modern world, and this state required millions of years. Until its scales cool, it is not one day as mentioned in Genesis